Glacier size changes in Kronotsky Peninsula and Alney-Chashakondzha Massif, Kamchatka Peninsula in the second half of XX century and the beginning of XXI century - A. Ya. Muravjev (Лëд и снег, 2015)
As it is known from recent investigations 448 glaciers are situated on the Kamchatka Peninsula, their total area are about 905 km2 [8]. More than 80% of them are glaciers of the Sredinny Range and the Klyuchevskaya group that is explained by large altitudes of them. Glaciers of the Kronotsky Penisula are less studied since this territory is practically not influenced by present-day volcanic processes. This paper presents results of investigation of changes in glaciations of the Kronotsky Peninsula and the mountain mass Alney-Chashakondzha (Fig. 1).The following materials are used: 1) the Landsat satellite picture of September 2nd, 2013; 2) pictures from satellite WorldView-2 of July 20th, 2010, and of August 1st, 2012 with spatial resolution of about 1 m; 3) aerial photographs made in August of 1950; 4) topographic maps of the 1:100 000 scale; 5) data from the USSR Glacier Inventory; 6) results of observations at hydrometeorological stations (HMS) Klyuchi and Kronoki (1950–2006) (www.meteo.ru).According to data from the USSR Glacier Inventory 32 glaciers were situated on the Kronotsky Peninsula, their total area 91.9 km2. By 2013, six glaciers disintegrated. Deciphering of the Landsat pictures did show 50 glaciers. Among them 23 glaciers are presented in the Inventory and they still hold their wholeness; 13 glaciers are segments of six disintegrated ones; 14 glaciers found in the pictures are not presented in the Inventory. Changes in areas of the Kronotsky Peninsula glaciers for period 1950–2013 in dependence on their sizes and expositions are shown in Tables 1 and 2.According to the Inventory 26 glaciers were situated in region of the Alney-Chashakondzha massif, their total area 61.4 km2. By 2010, four of them disintegrated. Deciphering of the World-View-2 picture of July 2010 did show 45 glaciers: 20 glaciers are consistent with the Inventory, and they hold their wholeness; 9 glaciers are segments of four disintegrated ones; 16 glaciers found in the pictures are not presented in the Inventory. Changes in areas of the Alney-Chashakondzha glaciers for period 1950–2013 in dependence on their sizes and expositions are shown in Tables 3 and 4.Glaciers on the Kronotsky Peninsula and the Alney-Chashakondzha massif shrink. Since 1950 to 2013 area of Kronotsky glaciers reduced by 18.8 km2, or by 22.9% (for glaciers with areas larger 0.5 km2). Area of the Alney-Chashakondzha glaciers reduced for the period since 1950 to 2010 by 11.6 km2, or by 19.2%, that is comparable to similar characteristics of glacier systems of Altai, Tien Shan, and Caucasus, and this contraction correlates with changes of basic climatic variations, i.e. rising of summer air temperature and decreasing of solid precipitation.